STRATEGI PENGGALI PASIR DALAM MENGATASI KEMISKINAN DI DESA SUKA DAMAI KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU - Saputri, Nopia; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the village of Suka Damai District Ujung Batu of Rokan Hulu. This study aims to determine how characteristics sand diggers in Desa Suka Damai, to know what are the factors that cause poverty in the sand diggers, and to determine strategies in resolve poverty in households sand diggers, this study is entitled: "Strategies Quarry Sand in Overcoming Poverty in the village of Suka Damai District Ujung Batu of Rokan Hulu ". The principal issues in this study is what factors cause the sand diggers poor and the strategies to overcome poverty they experienced. The samples in this research is using purposive sampling technique. Total population of the entire sand diggers are numbered 120 families (KK), a swab 30 families (KK) which has represented of the population that has been specified criteria. The method used is quantitative method with descriptive approach. Data filtering instrument used is observation, documentation and interview. The results have generally been carried out by the researcher, the researcher can say that the sand diggers in village Suka Damai poor, with the category of the amount of sand they produce in one day and also their income that amounted to 21 respondents (70%), they were only able bring and sells sand as much as 4-5 canoe in one day, and those with low educational factors also lead to poverty they are experiencing. The majority of the village of Suka Damai sand diggers have a strategy to anticipate their tough times, that is by doing side jobs, totaling 26 respondents (86.7%), they do a side job in hopes of reducing the burden of the family economy.Keywords: Sand diggers, Poverty, Strategy